identify the equivalent expression for each of the expressions below
![identify the equivalent expression for each of the expressions below class=](https://us-static.z-dn.net/files/dca/6eac26a78a3d0a96fbd6789ea6b32b90.png)
Answer: The answer is (c) [tex]x^\frac{1}{2}+3.[/tex]
Step-by-step explanation: We are given to identify from the options that which expression is equivalent to the expression below:
[tex]E=\sqrt{x}+3.[/tex]
We know that
[tex]\sqrt{x}=x^\frac{1}{2}.[/tex]
Therefore, the given expression becomes
[tex]E\\\\=\sqrt{x}+3\\\\=x^\frac{1}{2}+3.[/tex]
Thus, (c) is the correct option.